1978
DOI: 10.1111/j.1365-2141.1978.tb03662.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Specific Serum Iron in Thalassaemia: an Abnormal Serum Iron Fraction of Potential Toxicity

Abstract: Iron binding in the sera of 35 patients with beta thalassaemia major and intermedia was studied. In patients receiving regular blood transfusions since infancy transferrin was completely saturated and about 2.7--7.1 mumol/l of the serum iron could be removed by dialysis or ultrafiltration in the presence of a chelating agent or by filtration on DEAE-Sephadex-catecholdisulphonic acid columns. In contrast, less than 1.0 mumol/l of transferrin bound iron was removed when subjected to the same procedures. The non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
200
0
8

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(211 citation statements)
references
References 16 publications
1
200
0
8
Order By: Relevance
“…This is the reason why levels of NTBI in normal healthy individual do not exceed 1 lmol/L, and often undetectable by most of the methods [13]. In the iron overload scenarios like thalassemia; hemochromatosis and others iron gets a chance to exist in form which is not bond to Tf [2,[14][15][16][17][18]. Increased levels of NTBI in the above mentioned situations is easily explainable whereas it is difficult to give a convenient explanation for the raised levels of NTBI where Tf saturation is not high [18][19][20].…”
Section: Sources and Status Of Ntbi In Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the reason why levels of NTBI in normal healthy individual do not exceed 1 lmol/L, and often undetectable by most of the methods [13]. In the iron overload scenarios like thalassemia; hemochromatosis and others iron gets a chance to exist in form which is not bond to Tf [2,[14][15][16][17][18]. Increased levels of NTBI in the above mentioned situations is easily explainable whereas it is difficult to give a convenient explanation for the raised levels of NTBI where Tf saturation is not high [18][19][20].…”
Section: Sources and Status Of Ntbi In Circulationmentioning
confidence: 99%
“…Endogenous source is more important factor as iron absorption is well regulated at the mucosal level. In hemolytic anemia, increased endogenous inflow of iron due to excess haemolysis and/or compensatory blood transfusion may cause higher saturation of Tf leading to existence of NTBI [2,14,15,21]. Lee et al [22] reported the existence of NTBI in diabetes mellitus.…”
Section: Sources and Status Of Ntbi In Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to simple and sensitive assays that are performed under nearly physiological conditions, with 40-lM ascorbate added to initiate redox cycling of the iron and ensuing generation of reactive oxygen species (ROS) that are quantified by a fluorescence assay (Table I). Furthermore, unlike other studies [11,14,15], the LPI assay does not depend on supplementation of strong iron-mobilizing agents, or high-affinity chelators [16,20]. Thus, the assay avoids the inadvertent detection of TBI [15] or labile iron-chelates [19,[21][22][23].…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…Transition metals such as iron, and some iron-containing low molecular weight compounds play an important role in the generation of reactive oxygen species (ROS) and free radicals, which are supposed to damage cellular and subcellular structures and cause metabolic dysfunction [3,4,9,10,12,19]. Inter alia, the disturbed iron metabolism generates oxygen-derived free radicals in thalassemias.…”
Section: Introductionmentioning
confidence: 99%